The relationship between low thiol levels and major adverse cardiovascular events after primary percutaneous coronary intervention in patients with STEMI - Oğuz Akkuş; Mustafa Topuz; Hasan Koca; Hazar Harbalioğlu; Onur Kaypaklı; Mehmet Kaplan; Ömer Şen; Atilla Bulut; Hakim Çelik; Özcan Erel; Mustafa Gür (KARE Publishing, 2018)
Objective: The aim of this study was to investigate whether low thiol levels are associated with peri-procedural factors during primary percutaneous coronary intervention (pPCI) upon admission with ST-segment elevation myocardial infarction (STEMI), and the prognostic value at 6-month follow-up. Methods: A total of 241 consecutive acute STEMI patients who underwent pPCI and a control group of 67 individuals with a normal coronary angiography were enrolled in the study. Results: While age, contrast-induced nephropathy, N-terminal prohormone of brain natriuretic peptide (NT-proBNP), stent length, and creatinine were related to native thiol, NT-proBNP, contrast-induced nephropathy, and creatinine were related to total thiol. NT-proBNP was also related to the disulphide level. The left ventricular ejection fraction (LVEF) and the levels of native thiol, total thiol, low-density lipoprotein, and serum albumin were found to be independent predictors of major adverse cardiovascular events (MACEs) during 6 months of follow-up. Conclusion: Initial lower native thiol, total thiol, LVEF, LDL, and serum albumin may be used to identify patients with an increased long-term risk of unfavorable cardiac events in case of STEMI.